Efektivitas Pelaksanaan Business Development Service (BDS) dan Pemahaman Perpajakan Terhadap Kepatuhan Wajib Pajak UMKM (Studi Kasus Pada UMKM Pembibitan dan Budidaya Sapi Perah Batu) - Dewi, Farah Septya Findria; Mawardi, M. Cholid; Hidayati, Irma (e_Jurnal Ilmiah Riset Akuntansi, 2023)
This research was conducted due to a decrease in taxpayer compliance as of July 2022. The number of registered taxpayers reached 4.52 million, but only 1.1 million reported tax returns (SPT), and only 732 thousand corporate taxpayers actually paid taxes. This indicates the level of awareness or compliance of corporate taxpayers is still low. This decrease in taxpayer compliance shows a lack of understanding of taxation. Therefore, this research intends to analyze the effectiveness of the Business Development Service (BDS) program from various factors, such as planning, implementation and development, as well as understanding of taxation on taxpayer compliance in Micro, Small and Medium Enterprises (MSMEs). The method used in this research is qualitative by collecting data through interviews. The participants taken in this research were the managers of UMKM Batu Dairy Cattle Breeding and Cultivation and the KPP Pratama Batu Extension Team. The results of this research prove that planning, implementing, developing, and understanding taxation factors have an effective impact on increasing MSME taxpayer compliance, as shown in indicator SE-13/PJ/2018.Keywords: Business development service, planning factor, implementation factor, development factors, understanding of taxation.